Knowledge and perceptions of primary healthcare providers towards integration of antiretroviral therapy (ART) services at departmental levels at selected health facilities Lira district, Uganda - Puleh, Sean Steven; Ikwara, Emmanuel Asher; Namutebi, Syliviah; Nakero, Lakeri; Mwesiga, Godfrey; Isabirye, Rogers; Acen, Joy; Anyolitho, Maxson Kenneth (BioMed Central Ltd, 2023)
Abstract Background Investigations conducted among healthcare providers to assess their knowledge and perceptions towards the integration of anti-retroviral therapy (ART) related services in Sub-Saharan Africa are limited. This study explored the knowledge and perceptions of primary healthcare providers towards the integration of ART management services at departmental levels in health facilities in Lira district. Methods We conducted a descriptive cross-sectional survey that employed qualitative methods of data collection in four selected health facilities in Lira district between January and February 2022. The study involved in-depth interviews with key informants and focus group discussions. The study population consisted exclusively of primary healthcare providers; however, those who were not full-time employees of the participating health facilities were excluded. We used thematic content analysis. Results A significant proportion of staff (especially those who are not directly involved in ART) still lack full knowledge of ART services integration. There was generally a positive perception, with some suggesting ART integration can minimize stigma and discrimination. The potential barriers to integration included limited knowledge and skills for providing comprehensive ART services, insufficient staffing and space, funding gaps, and inadequate drug supplies, coupled with increased workload due to enlarged clientele. Conclusion Whereas healthcare workers are generally knowledgeable about ART integration, but their knowledge was limited to partial integration. The participants had a basic understanding of ART services being provided by different health facilities. Furthermore, participants viewed integration as critical, but it should be implemented in conjunction with ART management training. Given that respondents reported a lack of infrastructure, increased workload, and understaffing, additional investments in staff recruitment, motivation through training and incentives, and other means are needed if ART integration is to be implemented. Keywords: ART services, Readiness, Integration, Departments, Health facilities
Keywords: ART services, Readiness, Integration, Departments, Health facilities